New Species of Thalictrum (Ranunculaceae) from Okinawa Island in Japan and Its Phylogenetic Implications - Michimoto, Kanae; Yokota, Masatsugu; Abe, Atsushi; Fujii, Shinji; Takahashi, Daiki; Kakishima, Satoshi; Yu, Chih Chieh; Ito, Takuro; Maki, Masayuki (Phytotaxa, 2025)
This study aims to compare Thalictrum (Ranunculaceae) plant species, tentatively identified as T. minus, from the Yambaru region of Okinawa Island, Japan, with closely related species using morphometric and molecular phylogenetic analyses. Morphological observations revealed that the unique plants from Okinawa Island had clavate filaments and thickened roots. These traits differed significantly from those of typical T. minus, which have filamentous filaments and slender roots. Molecular phylogenetic analyses revealed that the unique plant on Okinawa Island is sister to T. urbaini, endemic to Taiwan, and formed a separate clade from those containing T. minus. Based on current morphological comparisons and molecular phylogenetic analyses, the unique plant on Okinawa Island was concluded to be a previously undescribed species, newly named Thalictrum yambaruense. Furthermore, our molecular phylogenetic analyses of Thalictrum in Japan and Taiwan revealed that T. tuberiferum var. yakusimense, endemic to Yakushima Island, Japan, is phylogenetically distinct from T. tuberiferum var. tuberiferum. Therefore, we propose elevating the taxonomic status of T. tuberiferum var. yakusimense to the species level as T. yakusimense.